PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 3 SOLOK SELATAN - Sari, Nova Devita; Emidar, Emidar; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThis article was written to illusstrate the effect of using technic mind mapping to writing skill of biography text of X students of SMA Negeri 3 Solok Selatan. This research data is a score in the skills of writing biography text before and after using technic mind mapping. This study has three results. First, the skills of writing biography texts before using technic mind mapping stay in the qualification Medium (SD). Second, the skill of writing the biography of the students of grade X SMA Negeri 3 Solok Selatan after using the technic mind mapping is qualified good (B). Third, based on the test concluded that there is significant technic mind mapping on the skill of writing biography text because thitung >ttabel (10,82>1,70).Â Kata kunci: pengaruh, teknik mind mapping, teks biografi